Saint Michael of the city [videorecording (DVD)] - Stewart, Jeff; Ratcliffe, Adam; Interdonato, Kevin; Interdonato, Kevin; Jacobs, Jensen; Wilson, Brian Anthony (Leomark Studios, 2024)
After being on the run from his checkered past, Michael is forced to return home, only to have his sins follow close behind. Eventually caught between his past life and new one, Michael is led to a collision course with destiny.